Implementing Digital Storytelling In Teaching Secondary School Students’ Speaking Skills of Narrative Text: A Case Study - Fitriana, Shafira Nur; Ambarwati, Evi Karlina; Kartini, Dedeh (Journal of Educational Sciences, 2024)
Digital Storytelling is a technology-enabled storytelling learning that facilitates 21st-century learning with effective, interactive, and collaborative learning encouraging learners to speak especially in speaking skills. This research was conducted to explore how technology-supported Digital Storytelling affects students' motivation and participation in speaking activities and find out the challenges and solutions faced when using this technology. The research used a descriptive case study. The participants of this study were 34 vocational high school students in Karawang. The research instruments were observation and interview to collect and the data was then analyzed using thematic analysis. The findings of this study revealed that students responded positively to learning English through Digital Storytelling using technology. However, some challenges were found in this study, such as facility challenges, teamwork, high desire to learn English, technological capabilities, and teacher challenges in teaching. Based on the study results, it can be concluded that despite the challenges, Digital Storytelling can provide positive responses to facilitate students’ learning to speak English.